Analisis Pandangan Aristoteles Tentang Lima Fungsi Bahasa Dalam Komunikasi - Gabriella, Fenika; Asyiffa, Asyiffa; sitorus, Fitzerald Kennedy (CV. ITTC INDONESIA, 2023)
Basically, humans have different characters, from one to another. So, these differences in character cause people to use language differently. Differences in using language cause the emergence of sounds that are not arranged based on a meaningful system. The aim of this research is to discuss Aristotle's views on the five functions of language and communication. This research uses a descriptive method with a literature review or literature study. The research results show that language as a communication tool is the most effective way to convey thoughts, aims and objectives to the people we communicate with. Language as a means of communication has the main function of language, namely that communication is the delivery of a message or meaning by someone to another person. The function of language as a tool of human communication includes five basic functions, namely expression function, information function, exploration function, persuasion function and entertainment function.